Associations of physical activity and sedentary behavior with cardiometabolic biomarkers in prediabetes and type 2 diabetes: a compositional data analysis. Issue 2 (2nd April 2020) - Rossen, Jenny; Von Rosen, Philip; Johansson, Unn-Britt; Brismar, Kerstin; Hagströmer, Maria
ABSTRACT: Objectives: To investigate the associations between objectively measured sedentary behavior (SB), light-intensity physical activity (LIPA) and moderate-to-vigorous physical activity (MVPA) and cardiometabolic and endocrine biomarkers, and to estimate the associations of reallocating time from one behavior to another with cardiometabolic and endocrine biomarkers. Methods: Baseline data from participants diagnosed with prediabetes or type 2 diabetes, n = 175, 58% men, mean (SD) age = 64.4 (7.7), recruited to a physical activity intervention was used. Time spent in SB, LIPA and MVPA was measured by accelerometer and transformed into isometric log-ratio coordinates. The associations between time spent in SB, LIPA and MVPA and biomarkers were examined by linear regression models. The change in each outcome of reallocating time between the three behaviors was estimated. Results: The findings show strong positive associations of time spent in MVPA and negative associations of time spent in SB relative to time spent in the other behaviors with sagittal abdominal diameter (SAD) and homeostasis model assessment for insulin resistance (HOMA-IR) and negative associations of time spent in SB with high-density lipoprotein (HDL) cholesterol. Theoretically, reallocation of 19 minutes MVPA to SB or to LIPA was associated with a 17% and 17% larger SAD, 39% and 36% larger HOMA-IR values and 3.3% and 2.3% lower levels of HDL, respectively. Conclusion: In conclusion, our analysis from a time-use perspective supports the current evidence that sedentary time is devastating for the cardiometabolic health. While LIPA probably requires more time, maintaining or increasing time in MVPA are the most important features of the time use behaviors when promoting a favorable cardiometabolic risk profile in adults with prediabetes and type 2 diabetes. Trial registration: ClinicalTrials.gov, NCT02374788. Registered 2 March 2015 – Retrospectively registered, https://clinicaltrials.gov/ct2/show/NCT02374788